A Performance Index as a Measure of the Host Suitability to Drosophila suzukii Matsumura (Diptera: Drosophilidae) - Dettler, María Antonela (2024)
Drosophila suzukii Matsumura, known as spotted wing drosophila (SWD), is an Asiatic invasive fruit pest that has spread over the world in the last 15 years, due to its high reproductive rate, its tolerance to different environmental conditions, the international fruit trade, and its wide range of host plants. In Buenos Aires, Argentina, blueberry is a major susceptible crop, although other cultivated and non-cultivated fruit species are frequent. The aim of this study was to evaluate the host suitability of commercial and non-cultivated fruit species (blueberries, plums, mulberries, and cherries) at two stages of maturity by estimating an index that takes into account biological and biometric parameters. The development and survival of SWD cohorts reared on different fruits were followed from egg to adult emergence. Then, adults were sexed and some biometric traits were measured. The indices: Wing loading, Wing aspect, and the Relative Performance Index (RPI) were estimated. The shortest developmental time and the maximum egg to adult survival were observed in the specimens developed in mulberry, in both stages of maturity. Only the length of the thorax showed significant differences between treatments in both sexes, and the largest adults were those reared in the ripe mulberries. The RPI, which relates performance and biometric variables, was the best index to evaluate the host suitability of SWD. So, it could be used as an indicator of the nutritional quality of fruits available in a region and to evaluate the importance of alternative hosts in the population dynamic of SWD.